The Effects of Body Percussion and Pattern Activity on the Creative Expression and Movement of Young Children - Laisiri, Kanpirom; Butkatunyoo , Oraphan; Samahito, Chalatip (Journal of Education Studies, Chulalongkorn University, 2024)
The purpose of this study was to study the expression and creative movement of young children who participated in a body percussion and pattern activity. The sample group consisted of 30 children aged 3-4 years who were studying in the second semester of the 2023 academic year. The sample group was obtained using cluster sampling. The instruments included 24 lesson plans incorporating body percussion and pattern activity to promote the creative expression and an assessment form movement of young children. The statistics used for data analysis were mean, standard deviation, t-test, and content analysis. The results of this study found that young children who participated in the activities had significantly higher scores in the expression and creative movement at the .05 level of significance, both overall and divided into the following aspects: 1) listening and distinguishing sounds from music, 2) listening to sounds from nature, and 3) using colors for movement and emotional expression. After instruction, children could listen to and distinguish the rhythms according to the music using symbolic pictures, create rhythmic sounds using their bodies and express their emotions by listening to the sounds of nature and music, and use colors to express the meaning of emotions. The body percussion and pattern activity to promote the creative expression and movement of young children could be applied to develop basic musical fundamentals and mathematics for young children.